George Eliot, Female Roles and education: an analysis of Middlemarch - Klering, Emily Haubert (Universidade do Vale do Rio dos Sinos, 2021)
Roles and expectations have traditionally shaped the lives of women. For a long time, gender determined where one would socially stand and the places they could go to (COSTA, 2020), and access to proper and meaningful education was denied. This research aims to analyse the relationship between women, knowledge, and authorship, as displayed in George Eliot’s Middlemarch (1871), under a feminist approach to literature (COSTA, 2020; ROCHA, 2016; ARMSTRONG, 2006; WEIL, 2006), considering the Victorian context in which the book was written. For this purpose, this thesis focuses on Rosamond, Dorothea and Mary, and their relationship with knowledge and education. From Rosamond’s traditional education and accomplishments to Dorothea’s desire for knowledge and Mary’s questioned authorship, it can be noticed that women’s abilities and capacities are frequently questioned in the novel. Furthermore, Dorothea’s desire to connect to a higher power through instructions is not fulfilled. The conclusion is that Eliot keeps her characters from achieving the enlightenment which she highly praises, advocating for better access whilst bound to the mindset which restrained girls from gaining complete independence and achieving remarkable things.
Keywords: George Eliot; Feminism; Education; Victorian Age; Middlemarch; George Eliot; Feminismo; Educação; Era Vitoriana